PERLINDUNGAN HUKUM TERHADAP HABITAT KOMODO DI PULAU KOMODO LABUAN BAJO NUSA TENGGARA TIMUR - Maria Anastasia Nangkur; Irawati, Arista Candra (Universitas Ngudi Waluyo, 2024)
Komodo Island in Labuan Bajo, East Nusa Tenggara (NTT), is home to the Komodo dragon (Varanus komodoensis), a protected rare species, one of the Seven Natural Wonders of the World. To maintain its preservation, given the threat to its habitat and the sustainability of its ecosystem. Law No. 5 of 1990 concerning the Conservation of Biological Natural Resources and Their Ecosystems and government policies related to the management of Komodo National Park. Several relevant laws and regulations are studied in this study through a descriptive-qualitative approach. The protection of Komodo dragon habitat on Komodo Island, the designation of Komodo Island and its surrounding area as Komodo National Park is an important step in protecting this habitat, including the regulation of conservation areas, the supervision of human activities, and the restriction of tourist access to prevent environmental damage. As a result, various conservation regulations and policies are strictly enforced. There are various laws and regulations that support legal protection, there are still some problems in its implementation. Legal protection must be balanced with stricter surveillance efforts and increased public and tourist awareness of the importance of preserving nature. Violations of the law such as illegal logging, poaching, and environmentally damaging fishing activities require the cooperation of the government, local communities, and non-governmental organizations to improve the supervision and enforcement system. The legal protection of Komodo dragon habitat on Komodo Island requires a comprehensive and integrated approach. ABSTRAK Pulau Komodo di Labuan Bajo, Nusa Tenggara Timur (NTT), adalah rumah bagi komodo (Varanus komodoensis), spesies langka yang dilindungi, merupakan salah satu dari Tujuh Keajaiban Alam Dunia. Untuk menjaga kelestariannya, mengingat ancaman terhadap habitatnya dan keberlanjutan ekosistemnya. Undang-Undang No. 5 Tahun 1990 tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya dan kebijakan pemerintah yang berkaitan dengan pengelolaan Taman Nasional Komodo. Beberapa peraturan perundang-undangan yang relevan yang dikaji dalam penelitian ini melalui pendekatan deskriptif-kualitatif. Perlindungan habitat komodo di Pulau Komodo, penetapan Pulau Komodo dan wilayah sekitarnya sebagai Taman Nasional Komodo merupakan langkah penting dalam melindungi habitat ini, mencakup pengaturan wilayah konservasi, pengawasan aktivitas manusia, dan pembatasan akses wisatawan untuk mencegah kerusakan lingkungan. Sebagai hasilnya, berbagai regulasi dan kebijakan konservasi diterapkan secara ketat. Terdapat berbagai peraturan per-undang-undangan yang mendukung perlindungan hukum, masih ada beberapa masalah dalam penerapannya. Perlindungan hukum harus diimbangi dengan upaya pengawasan yang lebih ketat dan peningkatan kesadaran masyarakat dan wisatawan tentang pentingnya mempertahankan kelestarian alam. Pelanggaran pertauran per-undang-undangan seperti logging ilegal, perburuan liar, aktivitas perikanan yang merusak lingkungan memerlukan kerja sama peningkatan sistem pengawasan dan penegakan hukum pemerintah, masyarakat lokal, dan organisasi non-pemerintah. Perlindungan hukum habitat komodo di Pulau Komodo memerlukan pendekatan yang komprehensif dan terintegrasi.